2018
DOI: 10.1111/cmi.12989
|View full text |Cite
|
Sign up to set email alerts
|

The Class IV human deacetylase, HDAC11, exhibits anti‐influenza A virus properties via its involvement in host innate antiviral response

Abstract: Histone deacetylase 11 (HDAC11) is most recently discovered deacetylase. Here, we demonstrate that human HDAC11 exhibits anti‐influenza A virus (IAV) properties. We found that knockdown of HDAC11 expression augments IAV growth kinetics in human lung epithelial cells A549 by up to 1 log. One of the ways HDAC11 exerts its anti‐IAV function is by being a part of IAV‐induced host antiviral response. We found that the kinetics of both IAV‐ and interferon‐induced innate antiviral response is significantly delayed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 41 publications
4
25
0
Order By: Relevance
“…Histone deacetylase 11 (HDAC11) is a class IV histone deacetylase, which is one of the most recently identified members of the HDAC family (Nutsford et al, 2019). HDAC11 has been shown to play a role in a variety of diseases including kidney ischemia and reperfusion (I/R) injury (Kim et al, 2013), cancer (Yue et al, 2020) and CVDs (Fan et al, 2018;Yuan et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Histone deacetylase 11 (HDAC11) is a class IV histone deacetylase, which is one of the most recently identified members of the HDAC family (Nutsford et al, 2019). HDAC11 has been shown to play a role in a variety of diseases including kidney ischemia and reperfusion (I/R) injury (Kim et al, 2013), cancer (Yue et al, 2020) and CVDs (Fan et al, 2018;Yuan et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The HDACs are a family of 18 members which are classified into four classes. We and others have found that at least one member of each class, including a class II member histone deacetylase 6 (HDAC6) [5,6] exhibits antiviral properties during IAV infection [7][8][9][10][11][12]. HDAC6 is a multi-substrate deacetylase with two catalytic domains [5,6] and has been shown to exert its anti-IAV function through multiple mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, a class IV HDAC member, HDAC11, has also been shown to exhibit antiinfluenza activity, probably by regulation of the IFN response [317].…”
Section: Mov10 and Ddx21: Antiviral Cellular Helicasesmentioning
confidence: 99%